Equity and justice in urban coastal adaptation planning: new evaluation framework - Tira Okamoto; Andréanne Doyon (Buildings & Cities, 2024)
Globally, cities and urban regions have initiated coastal adaptation planning to address increasing risk from sea level rise. However, there is growing awareness that sea level rise and other coastal flood risks will exacerbate existing social inequities if left unchecked. Planning scholars and practitioners have identified the importance of integrating an equity lens into their coastal adaptation planning, yet standards for defining and evaluating equity and justice in coastal adaptation planning have not been well outlined or applied. In response, more research is needed on tools for assessing processes and outcomes of equitable coastal adaptation planning. This paper asks: How are equity and justice being evaluated in urban coastal adaptation planning (UCAP)? The objectives are to: a) expand usages of equity and justice in UCAP and b) present a new framework for evaluating equity and justice within UCAP. The aim of the JustAdapt framework is to support UCAP scholars and practitioners in their pursuit of transformative urban adaptation, moving away from ‘checking the box’ on equity and toward just solutions. JustAdapt asks scholars and practitioners to disrupt dominant norms within the field and instead embrace reflexivity, accountability, and fluidity as they plan in relationship with the shifting tideline. Practice relevance Planning for sea level rise along urban shorelines presents an ever-changing challenge for urban coastal adaptation planning (UCAP) practitioners. Addressing equity and justice in UCAP adds another layer of complexity, as impacts from sea level rise will exacerbate historic and present inequities in coastal cities. This paper offers two main contributions: a) new understandings of equity and justice across five forms of justice – procedural, distributive, recognitional, intergenerational, and epistemic, and b) a new framework that can be used evaluate the degree to which equity and justice are integrated into a UCAP process. The JustAdapt framework supports practitioners to take actionable steps toward integrating equity and justice into their UCAP work, asking them to participate in the transition toward just urban adaptation.